A SYSTEMATIC LITERATURE REVIEW OF CARBURIZING PROCESSES IN STEELS: DIFFUSION MECHANISMS, PROCESS PARAMETERS, AND SURFACE PERFORMANCE - Reinaldo Evan Audrey; Bernadus Crisanto Putra Mbulu; Antonius Prisma Jalu Permana (Universitas Katolik Widya Karya Malang, 2026)
Carburizing is one of the most widely applied thermochemical surface treatments to enhance the mechanical performance of steels; however, existing studies remain fragmented, with limited integration of diffusion mechanisms, process parameters, and their combined effects on surface performance, which hinders process optimization for advanced applications requiring improved wear and corrosion resistance. This study addresses this gap through a systematic literature review (SLR) of approximately 28 peer-reviewed articles indexed in Scopus and ScienceDirect, using a structured methodology consisting of identification, screening, eligibility assessment, and comparative analysis focusing on key variables such as temperature, holding time, carburizing media, and diffusion behavior. The analysis shows that carbon diffusion kinetics and case characteristics are strongly influenced by process parameters, where temperatures of 850–950°C and longer holding times significantly increase case depth (up to >1 mm) and surface hardness (typically 50–65 HRC or improvements up to 150 HV). In addition, clear distinctions among carburizing methods were identified: gas and vacuum carburizing offer superior control of carbon potential and microstructural uniformity, while pack and liquid carburizing provide more economical alternatives with lower process precision. Notably, inconsistencies were found in correlating diffusion depth with corrosion resistance, indicating a critical research gap. This review establishes an integrated framework linking diffusion mechanisms, processing parameters, and surface performance, offering insights for optimizing carburizing processes and highlighting the need for future studies that simultaneously evaluate mechanical and corrosion properties.